POSITIVE INFLUENCE OF TELEVISION CARTOON PROGRAMS AMONG CHILDREN – ESPECIALLY FOCUSING ON BIODIVERSITY - M., Raghu Kalidasan; S., Shanmuga Mohana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Recently, there has been a change in perspective in how health, environmental, economic, and other social issues are perceived. The way people live, think, eat, and use technology has evolved into something more opulent and sophisticated. Like how high-rise construction and an increase in industry bring about numerous changes in geographical regions and climate-related changes in society. Understanding about these environmental issues is crucial for individuals from all walks of life, but it is especially urgent for kids. Since children are the society's future, it is crucial to raise their understanding of the environment and climate change.